Analisis Pengaruh Variabel Makroekonomi dan Jumlah Penerimaan Zakat di Indonesia: Implikasi Kebijakan Pemulihan Ekonomi Pasca Pandemi - Wirawan, Amaliyah; Hasdyani Putra, Muhammad Wicaksono; Sulaeman, Sulaeman (Management of Zakat and Waqf Journal (MAZAWA), 2022)
During the economic crisis both in 1998 and the current COVID-19 crisis, Indonesia experienced various economic and social problems as indicated by negative changes in economic growth and an increase in the number of poverty. In addition, zakat plays a very important role in assisting in the process of economic and social recovery after the crisis in Indonesia. This study aims to examine the effect of simultaneously and partially macroeconomic variables, namely inflation, exchange rates, gold prices, and the money supply on the amount of revenue and zakat in Indonesia. This research has used secondary data from 2016 – 2021 sourced from reports from Baznas, Bank Indonesia, BPS, and Precious Metals. Based on the results of data analysis using multiple linear regression, the results showed that the effect of the variable inflation rate, exchange rate, gold price, and the money supply simultaneously had a significant effect on the amount of zakat receipts. Partially, almost all variables have an effect except the price of gold, because the increase in the price of gold is inversely proportional to the increase in the amount of zakat funds received. The results of this study can be used as a reference for the government or policy makers in formulating policy materials in achieving the goals of the economic and social recovery process after the COVID-19 pandemic in Indonesia.